2004
DOI: 10.1038/sj.emboj.7600324
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of glycogen synthase: homologous enzymes catalyze glycogen synthesis and degradation

Abstract: Glycogen and starch are the major readily accessible energy storage compounds in nearly all living organisms. Glycogen is a very large branched glucose homopolymer containing about 90% a-1,4-glucosidic linkages and 10% a-1,6 linkages. Its synthesis and degradation constitute central pathways in the metabolism of living cells regulating a global carbon/energy buffer compartment. Glycogen biosynthesis involves the action of several enzymes among which glycogen synthase catalyzes the synthesis of the a-1,4-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
202
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(207 citation statements)
references
References 53 publications
5
202
0
Order By: Relevance
“…Glycogen consists of a-1,4-a-1,6-linked glucose residues (Manners, 1991), and serves as a major reserve polysaccharide in eukaryotes and in a variety of bacteria (Ball & Morell, 2003;Iglesias & Preiss, 1992). Although there have been some investigations of enzymes or genes involved in glycogen synthesis and degradation in other bacteria (Buschiazzo et al, 2004;Horcajada et al, 2006;Yeo & Chater, 2005), most studies have been done with Escherichia coli (Ballicora et al, 2003;Preiss, 1996). In this organism, glycogen is synthesized in a two-step process.…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen consists of a-1,4-a-1,6-linked glucose residues (Manners, 1991), and serves as a major reserve polysaccharide in eukaryotes and in a variety of bacteria (Ball & Morell, 2003;Iglesias & Preiss, 1992). Although there have been some investigations of enzymes or genes involved in glycogen synthesis and degradation in other bacteria (Buschiazzo et al, 2004;Horcajada et al, 2006;Yeo & Chater, 2005), most studies have been done with Escherichia coli (Ballicora et al, 2003;Preiss, 1996). In this organism, glycogen is synthesized in a two-step process.…”
Section: Introductionmentioning
confidence: 99%
“…Recent structural studies have shown that the enzyme folds into two Rossmann foldlike domains, with a deep cleft in between harboring the active site (1)(2)(3). Although the basic fold is conserved between the prokaryotic, archaeal, and eukaryotic enzymes, there are multiple sequence insertions in the eukaryotic enzymes.…”
mentioning
confidence: 99%
“…Although the initial stereochemical course of this reaction differs from that proposed in Fig. 4, since the protonation of D-glucal at C2 occurs from the a-side, we interpret this finding as the demonstration that a stable glucosyl derivative bearing a C1-C2 double bond is chemically and kinetically competent for the transfer reaction catalyzed by GP or MalP, whose active site machineries are very similar to that of GS and other retaining GTs of the GT-B fold (22). Remarkably, a glucose-derived intermediate also lacking the 1-hydroxyl group was found in the active site of MalP in a complex with maltopentaose and a phosphate ion, produced by rapid soaking and freezing (PDB 2asv).…”
Section: Discussionmentioning
confidence: 69%
“…Fungal and animal GSs, classed in family GT3, have only one representative, Saccharomyces cerevisiae GS, of known crystal structure (21), while three enzymes of the GT5 family, which comprises prokariotyc and archaeal GSs, as well as starch synthases, have been solved: those from Agrobacterium tumefaciens (22), Pyrococcus abyssi glycogen synthase (PaGS) (23), and Escherichia coli glycogen synthase (EcGS) (24). The crystal structure of the complex between EcGS and ADP-Glc showed that the enzyme is able to cleave its donor substrate into ADP and an unknown glucosyl species.…”
Section: Introductionmentioning
confidence: 99%